DEVELOPMENT OF PRIMARY EDUCATION IN UKRAINE FOR THE YEARS OF INDEPENDENCE - Hryshchuk, Halyna I. (Educological discourse, 2017)
The article examines the genesis of primary education in independent Ukraine; analyzed the modern types of schools in primary education; identified key trends and characteristics of education in independent Ukraine at various stages of historical development. Strategic direction of change in primary education in accordance with the new draft law of Ukraine «On Education» and the Concept of Primary Education are considered. Versatile development of children under the age of its features, spiritual and moral education of the individual it is the purpose of primary education. The main tasks of modern primary education are the following: psychological and pedagogical adaptation of the child to school; formation of the child, his spiritual, mental, physical and social development of cognitive abilities, interest in learning; formation of key competencies; creating a culture of communication and cooperation in various activities and forms of educational interaction, the ability to self-expression, social, legal, environmentally and safe behavior in various situations; forming an integral scientific world, emotional and value attitude to the child himself, other people, society and nature; aesthetic, moral and ethical, patriotic, civic, labor, environmental education of the child. It is concluded, that Ukrainian society needs creative thinking professionals who can effectively implement innovative technologies to improve the quality of the educational process.